2015
DOI: 10.3390/polym7111510
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of β-Glycerophosphate Crosslinking on Chitosan Cytotoxicity and Properties of Hydrogels for Vaginal Application

Abstract: Mucoadhesive gelling systems based on chitosan and chitosan/β-glycerophosphate (β-GP) were developed in order to increase clotrimazole residence time in the vaginal cavity. Ex vivo mucoadhesiveness using porcine vaginal mucosa followed with mechanical, viscoelastic, and swelling properties of prepared hydrogels were evaluated. Drug-free, sterile, unmodified, and β-GP crosslinked chitosan were investigated for the in vitro cytotoxicity in CRL 2616 human vaginal mucosa cells using MTT assay, fluorescent microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
3
28
1
Order By: Relevance
“…Based on the plotted trend line (Figure 3A), it was also noticed that unmodified chitosan and βGP/chitosan microparticles possessed comparable values ( p > 0.05) of F max . The obtained data is in agreement with results previously reported by our group, indicating that βGP modification of chitosan in semi-solid drug carriers maintained polymers’ ability to interact with mucosal tissue [35]. Nonetheless, the obtained W ad values were found to demonstrate a downward trend (Figure 3B) with raising the amount of ion cross-linker in chitosan microparticles.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the plotted trend line (Figure 3A), it was also noticed that unmodified chitosan and βGP/chitosan microparticles possessed comparable values ( p > 0.05) of F max . The obtained data is in agreement with results previously reported by our group, indicating that βGP modification of chitosan in semi-solid drug carriers maintained polymers’ ability to interact with mucosal tissue [35]. Nonetheless, the obtained W ad values were found to demonstrate a downward trend (Figure 3B) with raising the amount of ion cross-linker in chitosan microparticles.…”
Section: Resultssupporting
confidence: 91%
“…In addition, the obtained results demonstrated comparable viability of VK2/E6E7 cells within exposures to unmodified and βGP cross-linked chitosan microparticles. Interestingly, the above findings did not correspond with the cytotoxicity studies previously reported by our group in which lesser degrees of cytotoxicity had been noticed in VK2/E6E7 incubated with solutions of chitosan cross-linked with βGP (prepared by simple dissolution of the polymer in acetate buffer without further processing) [35], which might indicate that the applied spray drying process could have influenced the cytotoxicity profile of βGP/chitosan.…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…The viability of more than 85% cells in comparison with control group proved the biocompatible performance of the specimen. Vacanti et al [39] and Szymanska et al [40] demonstrated before that DEX and GP exhibit good biocompatibility in controlled one agent releasing vehicles, respectively. At the present research, it is shown that the dual releasing system of GP and DEX contain PVA coating enhanced biological properties of the anodized Ti.…”
Section: Cellular Interactionsmentioning
confidence: 99%